Nanowaste in the aquatic environment – threats and risk countermeasures - Bozena Mrowiec (Desalination and Water Treatment)
The rapid advancement of nanotechnology has led to an exponential increase in the production and application of engineered nanomaterials (ENMs) across diverse industries, inevitably resulting in the generation of nanowaste. As global markets for ENMs continue to expand (estimated grow from USD 26.16 billion in 2024 to USD 93.90 billion by 2032) the environmental release of nanoparticles (NPs) into aquatic systems poses emerging ecological and human health risks. Due to their high surface-area-to-volume ratio, reactivity, and colloidal stability, NPs exhibit complex environmental behaviors, including aggregation, transformation, sedimentation, and bioaccumulation. Their interaction with natural organic matter, metal ions, and aquatic biota can lead to speciation, toxicity, and mobility changes, affecting trophic transfer and ecosystem functions. Studies indicate that NPs induce oxidative stress, metabolic dysregulation, and genotoxicity in aquatic organisms, exacerbating concerns over water quality and biodiversity loss. Moreover, their ability to evade conventional water treatment processes necessitates the development of advanced remediation technologies, which remain cost-intensive and underregulated. Current regulatory frameworks for nanowaste management are insufficient, particularly in developing regions, complicating risk assessment and mitigation efforts. This brief review highlights the urgent need for interdisciplinary research on NP environmental fate, toxicity mechanisms, and remediation strategies. Strengthened regulatory policies, public awareness, and sustainable waste management approaches are critical to mitigating the long-term impacts of nanowaste on aquatic environments and public health.